APERSEPSI GURU DALAM PEMBELAJARAN BAHASA INDONESIA SISWA KELAS XI SMA NEGERI 1 SOPPENG: TEACHER'S APPERCEPTION IN LEARNING INDONESIAN LANGUAGE OF CLASS XI SENIOR HIGH SCHOOL 1 SOPPENG STUDENTS - Usman; Amelia, Risma; Sultan (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2023)
This research is a teacher's apperception research that aims to. to describe the form of teacher apperception in learning Indonesian for class XI students of SMA Negeri 1 Soppeng. The data in this study are verbal data from teachers in learning Indonesian, and the data source is in the form of learning activities carried out by Indonesian teachers during the learning process in class. Data collection is done by recording, observation, interviews. The results of this study reveal apperception form data. (1) alpha wave (student readiness to learn) has four parts, namely three data ice breaking, fun story, bring gym, music. (2) warmer, (3) pre-teach), (4) scene setting